Pediatric Primary Care : Well-Child Care. - Baker, Raymond C. (Core Handbook Series in Pediatrics., 2001)
Dr. Baker's widely used Handbook of Pediatric Primary Care has now been updated and expanded into two volumes-- Pediatric Primary Care: Well-Child Care and Pediatric Primary Care: Ill-Child Care . These practical handbooks provide easily accessible information on virtually every problem encountered in the primary care of children. Pediatric Primary Care: Well-Child Care focuses on health maintenance supervision and behavioral and developmental pediatrics. New chapters cover newborn screening, the sports physical, the adolescent visit, injury prevention, telephone medicine, and medical informat.